Management of testicular torsion by a general practitioner in remote Nepal: a case report - Dangal, Binod; Niraula, Satish; Chaudhary, Vivek (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: Testicular Torsion (TT) is the most common cause of acute scrotal pain in emergency setting in puberty age group. Delay in diagnosis and treatment lead to permanent necrosis of the testis. Rapid diagnosis and early exploration of the scrotum is the major step to salvage the testis.Clinical Case: A-14-year old male child with no significant comorbidity presented in emergency department with acute right sided scrotal pain and swelling for 12 hours with no history of fever and trauma. On examination, right testicular tenderness and swelling was noted along with positive Deming’s sign, negative Phren’s sign and absent cremasteric reflex. Doppler Ultrasound showed coarse echotexture with no vascularity in right testis. Emergency surgical exploration was done and the findings were necrotic right testicle with 5 times rotation. Right orchidectomy and left orcheopexy was performed in remote setting by a general practitioner.Conclusion: Testicular Torsion is the emergency condition of acute scrotal pain leading to permanent loss of testicle. Prompt surgical exploration is the cardinal point in treatment after proper diagnosis with Doppler Ultras.